PENGARUH KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT ADIKARA LESTARI NUSANTARA (MR. CREAMPUFF) SAWANGAN DEPOK - Amriyanti Puspita Sari, Meta; Maharani, Haidilia (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of placement and training on employee performance either partially or simultaneously at PT. Adiakara Lestari Nusantara (Mr.Creampuff) Area Depok. This research method uses quantitative methods with a descriptive approach. Data collection methods used are primary dataand secondary data. The sampling technique in this study used the Slovin technique, as many as 56 respondents. Data analysis using SPSS version 26 program. The analytical techniques used are validity test, reliability test, classic assumption test, normality test, multicollinearity test, heteroscedasticity test, auto correlation test, simple linearregression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test and hypothesis testing. Partial hypothesis testing of communication variable (X1) obtained tcount > ttable (2,509 > 1.660) and a significance value of 0.014 <0.05. This means that communication (X1) has a significant effect on employee performance (Y). The partial hypothesis test for the training motivational (X2) obtained a value of tcount > ttable (4,429 > 1.660) and a significance value of 0.000 <0.05. This means that the motivational (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained fcount > fable (22,133 > 3,091) and a significance value of 0.000 < 0.05. Soit can be concluded that communication (X1) and motivation (X2) have a significant simultaneous effect on employee performance (Y). Determination obtained R Square of 0.313, meaning that the variables of placement and training together have an influence contribution of 31.3% on employee performance. While the remaining 68.7% is influenced by other factors not examined in this study. Keyword: Communication, Motivational, Employee Performance